Етапи становлення української мови - Важинський, Б. В. (ХНУРЕ, 2019)
This article is aimed to reveal some peculiarities of the Ukrainian Language (its structure, nature, history); how Ukrainian language was formed; why it hasn’t come out of fashion for the previous 450 years; who and when became «the architects» of such melodious language.